Should We "Redshirt" in Kindergarten? A Study of the Effect of Age on Kindergarteners’ Reading Readiness - McNamara, John K.; Scissons, Mary; Simonot, Sheri (Alberta Journal of Educational Research, 2004)
This study examined the effect of chronological age on kindergarten children's reading readiness skills. Specifically, we ask whether chronological age should be considered when making decisions about academic redshirting: the practice of delaying younger children's entrance into kindergarten. We were concerned particularly with reading readiness because research has shown consistently that kindergarten children who demonstrate strong prereading skills such as phonological awareness and letter-sound understanding are more likely to become strong readers in later grades (Snow, Burns, & Griffin, 1998). The participants in this study were 625 kindergarten children who were measured for age, phonological awareness, and letter-sound understanding. Results of analysis indicate that younger children were no different from their older peers in their phonological awareness skills whereas significant between-group differences did occur for letter-sound understanding. These results give strength to the notion that younger children in kindergarten were comparable to older children in their phonological awareness skills. However, younger children were less skilled in understanding letter-sound relationships.